2017
DOI: 10.5483/bmbrep.2017.50.4.165
|View full text |Cite
|
Sign up to set email alerts
|

miR-374 promotes myocardial hypertrophy by negatively regulating vascular endothelial growth factor receptor-1 signaling

Abstract: Vascular endothelial growth factor (VEGF) is an essential cytokine that has functions in the formation of new blood vessels and regression of cardiac hypertrophy. VEGF/VEGF-receptor-1 (VEGFR1) signaling plays a key role in the regression of cardiac hypertrophy, whereas VEGF/VEGFR2 signaling leads to cardiac hypertrophy. In this study, we identified the prohypertrophic role of miR-374 using neonatal rat ventricular myocytes (NRVMs). Our results showed that overexpression of miR-374 activated G protein-coupled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In contrast, the VEGF/VEGFR2 signaling pathway accelerates cardiac hypertrophy. Lee et al found that miR‐374 inhibited the VEGFR1 signalling pathway and activated GPCR signalling pathway by targeting the 3′‐UTR of VEGFR1 and cGMP‐dependent protein kinase‐1 to mediated pro‐hypertrophic processes.…”
Section: The Role Of Mir‐374 In Cardiovascular Diseasementioning
confidence: 99%
“…In contrast, the VEGF/VEGFR2 signaling pathway accelerates cardiac hypertrophy. Lee et al found that miR‐374 inhibited the VEGFR1 signalling pathway and activated GPCR signalling pathway by targeting the 3′‐UTR of VEGFR1 and cGMP‐dependent protein kinase‐1 to mediated pro‐hypertrophic processes.…”
Section: The Role Of Mir‐374 In Cardiovascular Diseasementioning
confidence: 99%
“…miR-26 plasma concentration was shown to be associated with AMI [43]. miR-374 was shown to be pro-hypertrophic and to be involved in VEGF-receptor-1 signaling [44]. The miR-26 family plays an essential role in angiogenesis, epithelial cell growth and tissue repair [45].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, miR-374a has been suggested to regulate ATG5 [227]. MiR-374a has been linked to metabolic disorder during obesity [228] and can promote heart dysfunction by negatively regulating vascular endothelial growth factor (VEGF) receptor-1 signaling [229].…”
Section: Mirnas In the Regulation Of Autophagy Elongationmentioning
confidence: 96%